Effect of various reinforcements on properties of metal matrix composites: A review. (2020) - Meignanamoorthy, M.; Ravichandran, M.; Alagarsamy, S.V.; Chanakyan, C.; Dinesh Kumar, S.; Sakthivelu, S.
Abstract: Nowadays metal matrix composites (MMCs) playing an energetic role in engineering applications in the field of aerospace, automobile and structural despite of superior properties. The inclusion of various reinforcement into the metal matrix enhances the strength, hardness, stiffness and reduces the wear and density of the materials. This article made an effort to present the influence of various reinforcement such as B4 C, TiC, SiC, WC, Cr3 C2, Al2 O3, TiO2, ZrO2, SiO2, MoO3, MoS2, AlN, Si3 N4, ZrB2, TiB2 and Gr on the mechanical and tribological behavior of metal matrix. Foremost applications of various reinforcement with metal matrix are also emphasized in this work.